Concomitant fat embolism syndrome and pulmonary embolism in a patient with a femoral shaft fracture - Ebina, Masatomo (Acute Med Surg, 2015)
CASE: A 22‐year‐old man was injured in a traffic accident and developed respiratory distress on his first day of admission. On postadmission day 3, he developed serious respiratory distress with a suddenly altered mental status. Chest computed tomography revealed a pulmonary embolism that had not been evident when he was admitted. The patient was intubated and a continuous heparin infusion was started to treat the pulmonary embolism. Palpebral conjunctival petechiae were noticed the following day, at which point the patient fulfilled Gurd's criteria for fat embolism syndrome. Within a few days, his respiratory status was improved. Brain magnetic resonance imaging also provided evidence of fat embolism syndrome. His femoral shaft fracture was repaired on day 20. OUTCOME: The patient was discharged home on postadmission day 63. CONCLUSION: Concomitant fat embolism syndrome and pulmonary embolism, although very rare, should be considered when a trauma patient's respiratory status worsens.